Halal authentication using lateral flow devices for detection of pork adulteration in meat products: a review - Raja Nhari, Raja Mohd Hafidz; Jun, Hui Soh; Khairil Mokhtar, Nur Fadhilah; Mohammad, Nurhidayatul Asma; Mohd Hashim, Amalia (Taylor and Francis, 2023)
Lateral flow devices (LFDs) are straightforward scientific tools that have made substantial advances in recent years. They have been used in many fields including the meat industry to detect disease markers, determine meat freshness or meat species determination. They are, therefore, significant in the research of meat adulteration by mixed animal species, because food component authenticity is a serious concern encompassing health, economic, legal, and religious issues. Pork adulteration is one of the most crucial issues in the global meat industry. In this review, we discuss the various types of LFDs and recent research on the development of LFDs as an authenticity tool for detecting pig additives in meat-based products, and how regulatory authorities could adopt LFDs for their workflows. Despite the benefits of rapidity, simplicity, low cost, high sensitivity, and specificity, researchers face challenges when using LFD as a final confirmation test. Future directions are suggested for globalising the use of LFD as a halal authentication method.